Natural Electrotransformation of Lightning-Competent Pseudomonas sp. Strain N3 in Artificial Soil Microcosms - Cérémonie, Hélène (American Society for Microbiology, 2006)
The lightning-competent Pseudomonas sp. strain N3, recently isolated from soil, has been used to study the extent of natural electrotransformation (NET) or lightning transformation as a horizontal gene transfer mechanism in soil. The variation of electrical fields applied to the soil with a laboratory-scale lightning system provides an estimate of the volume of soil affected by NET. Based on the range of the electric field that induces NET of Pseudomonas strain N3, the volume of soil, where NET could occur, ranges from 2 to 950 m(3) per lightning strike. The influence of DNA parameters (amount, size, and purity) and DNA soil residence time were also investigated. NET frequencies (electrotransformants/recipient cells) ranged from 10(−8) for cell lysate after 1 day of residence in soil to 4 × 10(−7) with a purified plasmid added immediately before the lightning. The electrical field gradient (in kilovolts per cm) also played a role as NET frequencies ranging from 1 × 10(−5) at 2.3 kV/cm to 1.7 × 10(−4) at 6.5 kV/cm.